Effective non-drug interventions for improving outcomes and quality of maternal health care in sub-Saharan Africa: a systematic review. Issue 1 (December 2016) - Wekesah, Frederick; Mbada, Chidozie; Muula, Adamson; Kabiru, Caroline; Muthuri, Stella; Izugbara, Chimaraoke
Abstract Background Many interventions have been implemented to improve maternal health outcomes in sub-Saharan Africa (SSA). Currently, however, systematic information on the effectiveness of these interventions remains scarce. We conducted a systematic review of published evidence on non-drug interventions that reported effectiveness in improving outcomes and quality of care in maternal health in SSA. Methods African Journals Online, Bioline, MEDLINE, Ovid, Science Direct, and Scopus databases were searched for studies published in English between 2000 and 2015 and reporting on the effectiveness of interventions to improve quality and outcomes of maternal health care in SSA. Articles focusing on interventions that involved drug treatments, medications, or therapies were excluded. We present a narrative synthesis of the reported impact of these interventions on maternal morbidity and mortality outcomes as well as on other dimensions of the quality of maternal health care (as defined by the Institute of Medicine 2001 to comprise safety, effectiveness, efficiency, timeliness, patient centeredness, and equitability). Results Seventy-three studies were included in this review. Non-drug interventions that directly or indirectly improved quality of maternal health and morbidity and mortality outcomes in SSA assumed a variety of forms including mobile and electronic health, financial incentives on the demand and supply side, facility-based clinical audits and maternal death reviews, health systems strengthening interventions, community mobilization and/or peer-based programs, home-based visits, counseling and health educational and promotional programs conducted by health care providers, transportation and/or communication and referrals for emergency obstetric care, prevention of mother-to-child transmission of HIV, and task shifting interventions. There was a preponderance of single facility and community-based studies whose effectiveness was difficult to assess. Conclusions Many non-drug interventions have been implemented to improve maternal health care in SSA. These interventions have largely been health facility and/or community based. While the evidence on the effectiveness of interventions to improve maternal health is varied, study findings underscore the importance of implementing comprehensive interventions that strengthen different components of the health care systems, both in the community and at the health facilities, coupled with a supportive policy environment. Systematic review registration PROSPEROCRD42015023750